THE IMPERATIVES OF INCLUSIVE ECONOMIC GROWTH THEORY - O. Chaikin; T. Usiuk (Наукові горизонти, 2019)
Economic, social and ecological cohesion should remain at the heart of the global economy strategy to ensure that all capacities are mobilized and focused on the pursuit the inclusive development vector under the sustainable conditions. The purpose of the study is to investigate the evolution of development, formation and prospects of domestic economy development inclusive model implementation. The objectives of the study are: domestic inclusive economic growth model process generalization; existing approaches for inclusive growth measurement analysis; economic, social and ecological systemic changes in the domestic economic system justification. The methodological basis of the research is general scientific and special methods of economic phenomena and processes cognition. It has been determined that modern economic development is characterized by irregularity and represents extractive socio-economic system that limits equal access to opportunities, outputs and resources. The necessity of national inclusive development model implementation that would take into account the evolutionary ecological needs of the population and ensure the sustainability and competitiveness of the domestic economy, uniform population welfare increase has been shown. The expediency of own model of inclusive development design that would absorb the features of existing in the world models, but considering the ecological component, that will fit the concept of sustainable development has been substantiated. The modern tendencies of theoretical foundations and approaches to models of inclusive growth development have been defined. The Gini index of the countries rating was analyzed, on the basis of which the level of inequality of welfare of the population of Ukraine has been determined. The dynamics of the Gini Index in Ukraine change during the study period has been determined. Imperative knowledge about the inclusive economic growth model theory evolution has been systematized. The comparative analysis of existing approaches to inclusive growth measurement has been carried out. The number of systemic shifts to ensure equality of access to work outcomes changes and their equal distribution, taking into account the requirements of the sustainable development concept have been proposed. The possibility of introducing a comprehensive economic, social and environmental policy at the national and local levels has been considered. It has been determined that in the current context, the model of inclusive development is the most acceptable for Ukraine and is the basis for ensuring the sustainability and competitiveness of the domestic economy. The expediency of inclusive economic growth domestic model development and implementation has been substantiated. Further research should be aimed at design and scientific justification of inclusive economic development domestic model that would be capable to maintain high growth rates together with equal access to resources for all members of society provision.